Comprehensive and Personalized Care of the Hemodialysis Patient in Tassin, France: A Model for the Patient-Centered Medical Home for Subspecialty Patients. (22nd December 2012) - Anvari, Eva; Mojazi Amiri, Hoda; Aristimuno, Patricia; Chazot, Charles; Nugent, Kenneth
Abstract : The Centre de Rein Artificiel in Tassin, France, provides comprehensive care to patients with chronic renal disease similar to the model proposed for Patient Center Medical Homes; patients with end-stage renal disease in the Tassin Hemodialysis Center appear to have better outcomes than patients in the United States. These differences likely reflect this center's approach to patient-centered care, the use of longer dialysis times, and focused vascular access care. Longer dialysis times provide better clearance of small and middle toxic molecules, salt, and water; 85% of patients at the Tassin center have a normal blood pressure without the use of antihypertensive medications. The observed mortality rate in patients at the Tassin Center is approximately 50% of that predicted based on the United States Renal Data system standard mortality tables. Patient outcomes at the Tassin center suggest that longer dialysis times and the use of multidiscipline teams led by nephrologists directing all health care needs probably explain the outcomes in these patients. These approaches can be imported into the U.S healthcare system and form the framework for patient-centered medical practice for ESRD patients.